Islam in world politics - Johns, Anthony H. (Anthony Hearle); Lahoud, Nelly, 1972- (Routledge, 2005)
This book examines the influence of Islamist movements in national and international power politics, in the equilibrium of the world of finance, and the articulation of gender issues in Islamic and non-Islamic countries alike.